Cash flow based ratio vs. accrual based ratio / Shariful Amran and Ruslaina Yusoff - Amran, Shariful; Yusoff, Ruslaina (Universiti Teknologi MARA, Perlis & URDC UiTM Perlis, 2006)
This study was carried out to examine whether cash flow can be a good predictor to financially distressed companies. Thirty companies have been identified as financially distress companies based on the PN4 listing obtained from the Bursa Malaysia (MSE). The financial data of financially distress companies were studied over a period of ten years from 1993-2002. Cash Flow Based ratio and Accrual Based ratios were calculated using the financial data obtained from these companies. The study hypothesized that there is a difference in trend between Cash Flow based ratio and Accrual Based ratio for financially distress companies. Based on both the types of ratio calculated, trend analyses were conducted. It was found out that there is no obvious pattern obtained from the graph plotted using average figure for each type of ratio. Even though cash flow based ratio gives mixed results on its ability to predict financially distress company it is still useful for inter-company comparisons.